Sostenibilidad y Gestión de Proyectos como Claves de Competitividad en las MIPYMES de Honduras: Un enfoque basado en Estándares PMI - Reyes-Trejo, Annie Gissell; Figueroa-Hernández, Carlos; Delcid-Carrasco, Javier Enrique (LACCEI, 2025)
MICRO, SMALL, AND MEDIUM-SIZED ENTERPRISES (MSMES) IN HONDURAS PLAY A KEY ROLE IN THE HONDURAN ECONOMY AND FACE A CRITICAL CHALLENGE IN INTEGRATING SUSTAINABILITY PRACTICES INTO THEIR OPERATIONS. INTERNATIONAL ORGANIZATIONS SUCH AS THE UNITED NATIONS, THE WORLD BUSINESS COUNCIL FOR SUSTAINABLE DEVELOPMENT, THE INTERNATIONAL ORGANIZATION FOR STANDARDIZATION, AND THE GLOBAL REPORTING INITIATIVE PROMOTE REGULATORY FRAMEWORKS THAT GUIDE COMPANIES TOWARD THE IMPLEMENTATION OF ETHICAL AND RESPONSIBLE PRACTICES. THE MAIN OBJECTIVE OF THIS STUDY IS TO ANALYZE THE LEVEL OF IMPLEMENTATION OF SUSTAINABLE PRACTICES IN HONDURAN MSMES IN THEIR ORGANIZATIONAL, ECONOMIC, SOCIAL, AND ENVIRONMENTAL DIMENSIONS, AS WELL AS TO DETERMINE THE LEVEL OF ALIGNMENT OF THEIR OPERATIONS WITH THE PROJECT MANAGEMENT INSTITUTE (PMI).